Seismic modelling of early B-type pulsators observed by BRITE – I. θ Ophiuchi. Issue 3 (6th March 2019) - Walczak, Przemysław; Daszyńska-Daszkiewicz, Jadwiga; Pigulski, Andrzej; Pamyatnykh, Alexey; Moffat, Anthony F J; Handler, Gerald; Pablo, Herbert; Popowicz, Adam; Wade, Gregg; Weiss, Werner W; Zwintz, Konstanze
Abstract: We analyse time-series observations from the BRITE-Constellation of the well-known β Cephei type star θ Ophiuchi. Seven previously known frequencies were confirmed and 19 new frequency peaks were detected. In particular, high-order g modes, typical for the SPB (Slowly Pulsating B-type star) pulsators, are uncovered. These low-frequency modes are also obtained from the 7-yr SMEI light curve. If g modes are associated with the primary component of θ Oph, then our discovery allows, as in the case of other hybrid pulsators, to infer more comprehensive information on the internal structure. To this aim we perform in-depth seismic studies involving simultaneous fitting of mode frequencies, reproducing mode instability, and adjusting the relative amplitude of the bolometric flux variations. To explain the mode instability in the observed frequency range a significant increase of the mean opacity in the vicinity of the Z -bump is needed. Moreover, constraints on mass, overshooting from the convective core and rotation are derived. If the low-frequency modes come from the speckle B5 companion then taking into account the effects of rotation is enough to explain the pulsational mode instability.